Identification of cultural acculturation in the documentary film “Jelajah Budaya Tionghoa Nusantara” by DAAI TV - Sutandi, Septerianie; Selvia, Selvia (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2025)
Since 600 years ago, due to Indonesia’s very strategic position, Indonesia has become one of the centers of trade and cultural exchange in the Pacific Ocean. Because many traders from China landed in several areas in Indonesia, there were many phenomena of local cultural acculturation with Chinese culture. The acculturation process occurs because of social contact from one culture to another or the native culture with the culture of immigrants. This research is a qualitative descriptive research that analyzes the pattern of local cultural acculturation with Chinese culture in each episode of the documentary film "Jelajah Budaya Tionghoa Nusantara" produced by DAAI TV. The pattern of cultural acculturation was analyzed using Gillin and Gillin's theory. The results of this research show that local people in Indonesia who are open to other cultures but still maintain their own culture make the process of cultural acculturation run well. The most dominant factor in encouraging the acculturation of Indonesian Chinese culture is because of loyalty and social harmony. Tolerance between ethnic groups can be created through the open-mindedness of its people. Indonesian Chinese ethnic group, the government, and local people must move in one dynamic movement towards the same direction for the progress of the Indonesian nation.